2001
DOI: 10.1002/aic.690470605
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional wall jets: Axial flow in a stirred tank

Abstract: In this article, the flow at the wall of a stirred tank is compared with turbulent wall jet beha®ior. Agreement is shown to be ®ery good. For all three axial impellers studied, the wall jet is three dimensional along the wall and baffle of the tank. The expansion of the jet is linear, and the maximum ®elocity decays with 1rz, where z is the dimensionless axial distance. These wall-jet characteristics help further the fundamental understanding and modeling of the bulk flow in a stirred tank and pro®ide meaningf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 18 publications
2
21
0
1
Order By: Relevance
“…On the bottom the fluid diverges, changing its direction, and then travels upward along the vessel wall. Bittorf and Kresta (2001) showed that axial impellers drive four wall jets that propagate upward along the four baffles in the tank. The wall jets penetrate the bulk of the tank, involving two thirds of the tank volume in active circulation (Bittorf and Kresta, 2000).…”
mentioning
confidence: 98%
“…On the bottom the fluid diverges, changing its direction, and then travels upward along the vessel wall. Bittorf and Kresta (2001) showed that axial impellers drive four wall jets that propagate upward along the four baffles in the tank. The wall jets penetrate the bulk of the tank, involving two thirds of the tank volume in active circulation (Bittorf and Kresta, 2000).…”
mentioning
confidence: 98%
“…These velocities are similar in magnitude to the tip core velocities reported for axial impellers, which range from Ž . 0.210V to 0.326V Bittorf and Kresta, 2001 .…”
Section: U Mmentioning
confidence: 98%
“…impellers, which decays as 1rz Bittorf and Kresta, 2001 . In addition, the Rushton turbine is often placed at C sTr2, so the annular jet typically traverses only 0.5T, rather than the full height of the tank, as is the case for down pumping axial impellers.…”
Section: T T T Tmentioning
confidence: 99%
See 2 more Smart Citations